Level Of 25(OH)D Serum, Expression of Interleukin 4 And Glucocorticoid Receptor of Mononuclear Cell In Steroid Resistance Nephrotic Syndrome Children - Vonny Mariany Deckert; Loeki Enggar Fitri; Krsni Subandiyah (Journal of Tropical Life Science, 2015)
Nephrotic syndrome (NS) is autoimmune disease and its steroid resistance status supposed correlate with 25(OH)D level and IL-4 expression. The aimed of this study was investigated 25(OH)D plasma level, IL-4 and GR expression of PBMC in steroid sensitive and resistant pediatric NS patients and the association of those parameters. 27 subjects were divided into three groups (control group, steroid resistant NS group, and steroid sensitive NS group). Peripheral blood mononuclear cells (PBMCs) isolated using Ficoll-Hypaque method. Plasma 25(OH)D level was measured using ELISA method. IL-4 and GR expression were measured using flowcytometry of PBMCs. This study showed that 25(OH)D level and GR expression were significantly different in control group compared to steroid resistant NS group (p<0.05). Plasma 25(OH)D level, IL-4 and GR expression were not correlated each other in NS patients (p>0.05). Plasma 25(OH)D level, IL-4 and GR expression were not contributed in steroid resistance in NS patients. However, GR expression has highest contribution in steroid resistance of NS patient (Wald score 1.198). Plasma 25(OH)D level and GR expression was lower in steroid resistant NS group. GR expression has a highest contribution in steroid resistance of NS patients.